Vagabond life : the Caucasus journals of George Kennan - Kennan, George, 1845-1924 (Donald R. Ellegood International Publications., 2003)
"George Kennan (1845-1924) was a pioneering explorer, writer, and lecturer on Russia in the nineteenth century, the author of classic works such as Tent Life in Siberia and Siberia and the Exile System, and great-uncle of George Frost Kennan, the noted historian and diplomat of the Cold War. In 1870, Kennan became the first American to explore the highlands of Dagestan, a remote Muslim region of herders, silversmiths, carpet-weavers, and other craftsmen west of Chechnya, only a decade after Russia violently absorbed the region into its empire. He kept detailed journals of his adventures, which today form a small part of his voluminous archive in the Library of Congress. Frith Maier has combined the diaries with selected letters and Kennan's published articles on the Caucasus to create a vivid narrative of his six-month odyssey.The journals have been organized into three parts. The first covers Kennan's journey to the Caucasus, a significant feat in itself. The second chronicles his expedition across the main Caucasus Ridge with the Georgian nobleman Prince Jorjadze. In the final part, Kennan circles back through the lands of Chechnya to slip once again into the Dagestan highlands.Kennan's remarkable curiosity and perception come through in this lively and accessible narrative, as does his humor at the challenges of his travels."